Toxoplasmic retinochoroiditis presenting in childhood: clinical findings in a UK survey. Issue 12 (9th August 2006) - Stanford, M R; Tan, H K; Gilbert, R E
Abstract : Aim: To compare the clinical findings in children with symptomatic toxoplasmic ocular lesions attributable to infection acquired before or after birth. Methods: Cases were prospectively ascertained for 24 months through national surveillance units and reference laboratories in the British Isles. Age and presenting symptoms, site of lesion and visual impairment in children who were classified as acquiring infection either before or after birth on the basis of clinical and serological findings were compared. Results: 31 children had toxoplasmic retinochoroiditis, 15 had congenital infection and all but three of these presented before the age of 4 years. The remaining 16 children acquired toxoplasmosis postnatally, and 14 of 16 presented after the age of 10 years. A further four children had retinochoroiditis due to other causes. The presence of bilateral, multiple or posterior pole lesions did not distinguish between the two groups, but most children (16/19; 84%) presenting with acute ocular symptoms had postnatally acquired infection. Unilateral visual impairment (Snellen ⩽6/18) was equally prevalent in the two groups (4/9 before birth v 7/16 after birth; p>0.5). Only two children had bilateral visual impairment, both of whom had congenital infection. No child was blind. Conclusions: About 50% of children with ocular lesions due to toxoplasmosis had postnatal infection. Retinochoroidal lesions due to infection before and after birth were indistinguishable. The prognosis for bilateral visual function was good, regardless of when infection was acquired.